Case Report: Robot-assisted laparoscopic nephron-sparing surgery for a renal abscess mimicking a tumor - Wang, Shun; Liang, Xiangyi; Pan, Di; Zhang, Jianqing; Chen, Kun; Jiang, Kehua; Li, Tao (Frontiers in Oncology, 2022)
The differential diagnosis of renal tumors and abscesses is crucial owing to their different treatments. Although antibacterial administration and radiological examination are excellent means for distinction, misdiagnosis is common and may lead to severe consequences, such as the need for nephrectomy. Herein, we report a case involving a 52-year-old Asian woman with a renal mass for which a differential diagnosis was challenging. The mass persisted after administration of intravenous antibiotic therapy for 1 month. A computed tomography scan indicated an inflammatory lesion, whereas magnetic resonance imaging suggested a diagnosis of a tumor. Despite these indications, a right renal abscess was suspected during robot-assisted laparoscopic surgery, and nephron-sparing surgery was performed, which allowed confirmation of the final pathological result by biopsy specimen. Postoperatively, the mass gradually decreased in size after antibiotic therapy for a further month. This case, in which a renal abscess mimicked a tumor and the patient almost underwent a nephrectomy, highlights the need for caution in establishing therapeutic schedules for patients with inaccurate diagnoses. The management strategies for such patients must be reviewed and improved.